Matriz de procesos críticos: Propuesta para estudiar condiciones de vida y salud (2007)
ABSTRACT: To present theoretical methodological elements for the study of life and health conditions in the municipality of Marinilla, Colombia, based on a critical processes matrix. Material and methods: Historical documentary analysis, application of familiar cards to 4284 families, workshop meetings with communitarian and institutional leaders, interviews to principal actors and analyses of municipal plans and programs. Results: Protective conditions: cultural wealth, conservation of artistic traditions; house projects; the municipality has environmental promoters and administrators of aqueducts, programs managers and promoters of health. Conditions of deterioration: Dimension of the work: Urban and rural groups suffering high deterioration, great labor instability, low qualification, extensive labor days. Dimension of consumption: Spoiled urban and rural groups and homelessness; rural groups without electrification and living in dilapidated houses. Environment: environmental pollution specially in the poorest districts; spoiled rural groups; polluted water sources and deforestation. Health disease process: Common problems: infantile undernourishment, respiratory diseases and acute diarrhea, arterial hypertension, diabetes, cancer; poisonings by pesticides, injuries, accidents, sexual abuse, violent death; greater frequency in rural groups with higher deterioration. Conclusions: The matrix is a useful theoretical-methodological proposal for social investigators, health and municipal administrators, because it articulates the knowledge of the population needs differentiated by groups, political projects and the monitoring of life conditions through participant processes.